Methotrexate-loaded Sr-BDC metal-organic frameworks attenuate glioblastoma and cervical-carcinoma cells and spheroids' growth and motility by reducing the inflammation-EMT axis and inducing apoptosis - Yildirim, Eren; Sengelen, Aslihan; Yucel, Oguz; Aksut, Yunus; Ogutcu, Irem; Bayrakci, Atahan; Gencel-Guler, Ceren; Gunes, Utku; Ildes, Caner; Pekmez, Murat; Emik, Serkan (ELSEVIER, 2025)
Metal-organic frameworks (MOFs) show promise for anticancer drug delivery. This study investigates the efficacy of strontium (Sr)-based MOFs for delivering methotrexate (MTX, folate analog) to folate receptor (FR)positive U-87MG/glioblastoma and HeLa/cervical-carcinoma cells and spheroids. Herein, Sr-based MOFs with terephthalic acid (BDC) were synthesized via flow-controlled solvothermal synthesis to generate MTX-loaded nanoparticles (NPs) for the first time. SEM, TEM, DLS, DSC, and FTIR analyses revealed that NPs had threedimensional structure, nanoscale particle size (similar to 100 nm), narrow size distribution, and good stability. Confocal microscopy confirmed their penetration into U-87MG glioblastoma and HeLa cervical-carcinoma cell monolayers and spheroids. MTT results (treatment-time:1-h, analysis at 48-h and 72-h) showed that bound-MTX was more effective at lower doses than free-MTX, with increased drug sensitivity (3.72 and 15.94 for U-87MG, 6.25 and 31.25 for HeLa cells, respectively). MTX/Sr-BDC MOFs had negligible penetration into FR- HEK-293 normal cells and low toxicity. Remarkably, MTX/Sr-BDC MOFs (treatment-dose/time: 2.5 mu g/mL MTX/1-h, analysis at 48-h) significantly downregulated inflammation (decreased NF-kappa B-p65, IL-1R, IL-6, TNF-alpha, and increased IL-10 levels)/epithelial-mesenchymal transition (EMT; decreased N-cadherin/E-cadherin ratio and Snail, Twist1, TGF-R levels) axis, reduced migration/colony-formation ability, and induced apoptosis. Moreover, tumor growth in 3D-spheroids (mimicking in vivo tumors) treated with MTX/Sr-BDC MOFs was observed to slow down significantly based on dose (2.5-25 mu g/mL) and time (2 and 7-days), with reduced viability compared to untreated or free-drug groups. These outputs indicate that Sr-based MOFs could serve as a delivery system for MTX in treating aggressive glioblastoma and cervical tumors by targeting the inflammation-EMT axis and inducing apoptosis.
Keywords: Metal-organic frameworks (MOFs); Strontium (Sr); Methotrexate (MTX); Cancer therapy; Glioblastoma; Cervical-carcinoma; E-CADHERIN EXPRESSION; DRUG-DELIVERY; NANOPARTICLES; STRONTIUM; THERAPY; MECHANISMS; MIGRATION; EFFICACY; PATHWAY; GLIOMAS; Pharmacology & Pharmacy